Geochemical characterization of humic acids isolated from tundra lakes sediments of Murmansk region, Russia - Alina V. Guzeva; Zakhar I. Slukovskiy (Water sector of Russia problems technologies management, 2023)
Humic substances play an important role in the biogeochemical cycles of terrestrial and aquatic ecosystems. Study of these substances is necessary to consider the fundamental processes of humification in various climatic zones. Data on the composition and structure of humic acids in lake sediments are limited and do not cover water bodies in cold-water regions. Th e study focuses on the comprehensive research of geochemical and environmental features of humic acids isolated from sediments of small tundra lakes (the Rybachiy and Sredniy Peninsulas, Murmansk region).